Digital Trade and WTO Accessions: “I Can Live, With or Without You” - Guglya, Leonila (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2025)
The process of accession to the World Trade Organization (WTO) is highly demanding, requiring deep reforms of domestic legal and institutional frameworks. While accession packages have not yet systematically included rules on digital trade, this area is increasingly central to modern commerce. The article explores two main points: why this gap exists and how it could be bridged. It reviews the scope of digital trade, covering electronic transactions, electronic payments, data governance, online consumer protection, and technology regulation, among others, and shows how current WTO agreements indirectly support it. Beyond these, the 1998 Work Programme on E-commerce and the WTO Joint Initiative on Electronic Commerce, as well as the other Joint Statement Initiatives, provide additional frameworks and spaces for deliberations and experience-sharing between all or a subset of the WTO Members. For governments in the process of accession—many of them developing economies—digital trade presents both opportunities and barriers, ranging from infrastructure and regulatory deficits to capacity and coordination challenges. The article argues that integrating digital trade into accession strategies could strengthen domestic reforms, attract technical assistance, and better position new members to shape the evolving digital trade agenda, while also raising questions about the risks of overburdening accession packages.